Relationships between aerosol, cloud, and precipitation as observed from the A-train constellation of spaceborne sensors - Lebsock, Matthew David, author; Kummerow, Christian D., advisor; Stephens, Graeme L., 1952-, advisor; Randall, David A. (David Allan), 1948-, committee member; Reising, Steven C., committee member (Colorado State University. Libraries, 2009)
Data from several sensors flying in NASA's A-train constellation of satellites are analyzed to examine global relationships between aerosol, clouds and precipitation with particular emphasis placed on the Earth's radiation budget. The multi-sensor data are applied to two specific studies. The first addresses the response of cloud water path to atmospheric aerosol burden and the second quantifies relationships between tropical precipitation and radiation within the context of radiative-convective equilibrium. The first focused study presents a global multi-sensor satellite examination of aerosol indirect effects on warm oceanic clouds. The study centers on the water path response of cloud to aerosol burden. It is demonstrated that high aerosol environments are associated with reduced liquid water path in nonprecipitating clouds and that the reduction in liquid water path reduces the albedo enhancement expected from decreasing effective radius. Furthermore the reduction in liquid water path is greater in thermodynamically unstable environments than in stable environments, suggesting a greater sensitivity of liquid water path to aerosol in cumulus clouds than stratus clouds. In sharp contrast with nonprecipitating clouds, the cloud liquid water path of transitional and precipitating clouds increases dramatically with aerosol, which may be indicative of an inhibited coalescence process. Following from these observations, the magnitude of the aerosol indirect albedo sensitivity (IAS) is calculated as the sum of distinct cloud regimes over the global oceans. Selection of the cloud regimes is guided by the observation that both thermodynamic stability and the presence of precipitation affect the sensitivity of cloud albedo to aerosol concentrations. The IAS, defined as the change in warm cloud albedo for a fractional change in aerosol burden, is found to be -0.42 ±0.38 Wm-2 over the global oceans. Twenty five percent of the effect is due to precipitating clouds despite the fact that only eight percent of clouds are identified as precipitating. An additional assumption of the anthropogenic aerosol fraction provides an estimate of the indirect albedo forcing (IAF) of -0.13 ± 0.14 Wm-2, which is significantly lower than the range provided by climate model estimates. The second focused study presents an analysis of anomalous precipitation, cloud, thermodynamic, and radiation variables on the tropics-wide mean spatial scale. In particular, relationships between the mean tropical oceanic precipitation anomaly and radiative anomalies are examined. It is found that tropical mean precipitation is well correlated with cloud properties and radiative fields. In particular, the tropical mean precipitation anomaly is positively correlated with the top of the atmosphere reflected shortwave anomaly and negatively correlated with the emitted longwave anomaly. The tropical mean relationships are found to primarily result from a coherent oscillation of precipitation and the area of high-level cloudiness. The correlations manifest themselves radiatively as a modest cooling at the top of the atmosphere and a redistribution of energy from the surface to the atmosphere through reduced solar radiation to the surface and decreased longwave emission to space. The anomalous atmospheric column radiative heating is found to be about 10% of the magnitude of the anomalous latent heating. The temporal signature of the radiative heating is observed in the column mean temperature that indicates a coherent phase-lagged oscillation between atmospheric stability and convection. These relationships are identified as a radiative-convective cloud feedback that is observed on intra-seasonal timescales associated with the Madden-Julian oscillation in the tropical atmosphere. A composite analysis showing the spatial patterns of the anomalies provides evidence that the feedback mechanism works through a modulation of the strength of the large-scale tropical overturning circulations.
Department Head: Richard Harlan Johnson.